PROFITABLE HIGH-SPEED PASSENGER VESSEL FOR SHORT LINES AT SEA - Dubrovsky, Victor A. (International Journal of Research -GRANTHAALAYAH, 2020)
The paper [1] had presented an alternative option of outrigger high-speed passenger vessel for short lines. Such ships can compete with existed ones from economy point of view if the firsts will have minimal cost of building and minimal operation price, firstly – because of minimal outlay of fuel, but for comparable service speed and capacity of passengers. Besides, usually small enough vessels are strongly affected by weather, by waves in main. It means, seaworthiness of such ships is a permanent problem if they must operate at more or less severe conditions of weather. Two newly proposed options of outrigger ships are described below: the first has small water-plane area of the main hull bow, and the second has small water-plane area of the main hull as a whole. The selection of the main dimensions are shown in main, the results are discussed from seaworthiness point of view. Both new options are recommended for further designing, including researching of motion characteristics and possible economy results.